Sistem Penerjemah Bahasa Jawa-Aksara Jawa Berbasis Finite State Automata - Banu Wirawan Yohanes; Teofilus Robert; Saptadi Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Current Javanese script translators still have many shortcomings, both in completeness and procedure for their script writing. These are caused by the difficulty of applying the rules of writing in translating Javanese script. This paper proposes a hyphenated method for Javanese words into syllables using finite state automata. The Javanese to Javanese script and vice versa translator web application development was implemented using Unicode standard Javanese script based on Graphite feature. Translator testing was carried out by teachers who have Javanese expertise. The test results indicate that the translator is able to translate in most cases, which are 92% for the translation of Javanese to Javanese script and 93.8% for the translation of Javanese script to Javanese.